2012
DOI: 10.5601/jelem.2009.14.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Activity of dehydrogenases, catalase and urease in copper polluted soil

Abstract: Copper is a life essential element. However, in excess it can be destructive to metabolism of microbial, plant, animal and human cells. Thus, an understanding of all conditions associated with the effect produced by copper on natural environment is vital. The purpose of the present study has been to evaluate the effect of soil contamination with copper on the activity of dehydrogenases, catalase and urease as well as to determine the tolerance of these enzymes to excessive amounts of copper in soil. The variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…According to Wang et al (2007), copper applied in the amount of 658 mg kg -1 inhibited the activity of microorganisms in soil and thus limited the uptake of the substrate, the formation of the enzyme and the absorption of the generated product by microorganisms. Therefore, it is frequently accepted that dehydrogenases reflects the biological state of soil in the most exact manner (Wyszkowska et al 2009; Ge and Zhang 2011). However, copper had a comprehensive effect on the enzymes, which is proven by the strong inhibition of urease activity, and urease is both an intraand extracellular enzyme, with as much as 80-90% of it being able to form complexes with soil colloids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Wang et al (2007), copper applied in the amount of 658 mg kg -1 inhibited the activity of microorganisms in soil and thus limited the uptake of the substrate, the formation of the enzyme and the absorption of the generated product by microorganisms. Therefore, it is frequently accepted that dehydrogenases reflects the biological state of soil in the most exact manner (Wyszkowska et al 2009; Ge and Zhang 2011). However, copper had a comprehensive effect on the enzymes, which is proven by the strong inhibition of urease activity, and urease is both an intraand extracellular enzyme, with as much as 80-90% of it being able to form complexes with soil colloids.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Kucharski and Wyszkowska (2004) also showed that a toxic effect which involves disruption of water balance (wilting), chlorosis of young leaves and damaging of the apex and roots in spring barley was stronger in plants grown on leached brown soil formed from light loamy sand than on leached brown soil formed from light loam. Regardless of the physicochemical properties of soil, contamination of soil with copper has a negative effect of plant growth, disrupting electron transport and decreasing the rate of photosynthesis (Zhang et al 2014) and results in a yield decrease (Wyszkowska et al 2009;Girotto et al 2013). When copper levels in soil increase and it is taken up by plants, it is fixed in roots by phytochelatins, and only small amounts are accumulated in the above-ground parts (Kotrba et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that urease was less affected by heavy metals, which may be caused by the difference of soil properties (Wyszkowska et al 2009;Khan et al 2007).…”
Section: Pcr-dgge Fingerprinting Analysismentioning
confidence: 99%
“…Por ejemplo, la alta concentración de Cadmio (40 mg Cd/kg de suelo) inhibió la tasa de crecimiento microbiano, la fosfatasa ácida del suelo, la fosfatasa alcalina y a la ureasa (Renella et al, 2006). Una mayor concentración de Cu (150 a 450 mg / kg de suelo) inhibió significativamente las deshidrogenasas del suelo, ureasa y catalasa (Wyszkowska et al, 2009). Los metales pesados causan disminución significativa del crecimiento de la planta y el contenido de proteína a altas concentraciones.…”
Section: Consecuencias De La Contaminación Química Y Biorremediaciónunclassified